Formation of Silver Nanoparticles Using Phyllantus buxifolius Leaf Extract and Its Antioxidant Activity - Dini Hanifa; Purnawan Pontana Putra; Akmal Djamaan; Marta Aulia Zahra; Maharani Auliasanrah Siregar (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2026)
Green synthesis is an approach for producing silver nanoparticles (AgNPs) that more popular because the use of bioreductor, making it safer and more eco-friendly. The use of Phyllanthus buxifolius as a source of reducing and stabilizing agents in the formation of AgNPs and its contribution to antioxidant activity is still limited. Therefore, this study aims to synthesize AgNPs using P. buxifolius leaf extract and evaluate its antioxidant activity. The leaves of P. buxifolius were extracted using ethanol in a 1:10 ratio through maceration, then followed by solvent evaporation using a rotary evaporator. AgNO3 was mixed with a 10% P. buxifolius leaf extract solution. The UV-Vis spectrum was analyzed at wavelengths ranging from 400 to 800 nm. Particle size, morphology, functional groups, and crystal structure of AgNPs were characterized. Antioxidant activity was assessed using the DPPH method to determine the IC50, with ascorbic acid as the reference standard. To confirmed the formation of silver nanoparticles, a color change from colorless to brown were observed. These nanoparticles exhibited a Surface Plasmon Resonance (SPR) peak at 420 nm, were non-spherical with the particle size around 50 nm, and showed a crystalline structure. Additionally, the silver nanoparticles synthesized with P. buxifolius extract demonstrated comparable antioxidant activity to standard ascorbic acid, indicating their potential to be developed as antioxidant agents for health and therapeutic uses.